Effectiveness of sonography assisted minimal invasive plate osteosynthesis (MIPO) compare with fluoroscope assisted in femoral shaft fracture: A cadaveric study - Saengsin J. (2017)
© 2017 Elsevier Ltd Introduction A minimal invasive plate osteosynthesis (MIPO) has an advantage of biological soft tissue preservation that consists of preserving bony blood supply, fracture hematoma and less soft tissue damage which leads to decreasing of infection rate and rapid bone healing. However, the radiation exposure is still a disadvantage of this technique. A sonography that provides dynamic real time imaging may be used as an alternative technique for assisting MIPO. The aim of this study was to compare the effectiveness of MIPO in femoral shaft fracture between the sonography assisted and the fluoroscopy assisted. Methods Twenty-eight cadaveric limbs were subjected to create femoral shaft fracture. Then, sonography assisted reduction with temporary external fixation and MIPO were performed. Images of the sonography and the fluoroscopy were recorded including before reduction, after reduction and after MIPO in order to identify fracture displacements in anteroposterior and mediolateral directions. Moreover, the anterior and posterior distances from edge of the bone to the plate were measured to confirm plate position. The effectiveness of this technique was defined as the proper plate position and acceptable alignment after fixation. All distances from the sonography and the fluoroscopy were also analyzed and compared using Pearson correlation and Bland-Altman method to assess the agreements between two tests. Result All of the subjects were met the criteria for acceptable alignment. We found only three femoral shaft fracture (11%) operated with MIPO by sonography assisted that showed slipped plate off femoral bones. According to Pearson correlation, there were good to excellent agreements in term of measuring fracture displacement before (Pearson Correlation > 0.7) and after reduction (Pearson Correlation > 0.7) between these two tests. There was moderate agreement regarding to evaluation of plate position (Pearson Correlation 03.–0.7). When we compared two methods of measurement using Bland-Altman plot, there were no statistical significant difference (P < 0.05). Conclusion Images from the sonography could provide visualization of the fracture during reduction and MIPO as accurately as the radiography. Thus, the sonography assisted MIPO in femoral shaft fracture can be done effectively comparing with radiographic assisted.